MONITORING OF EGRESS OF “ESCOLA DO TRABALHADOR” IN THE BRAZILIAN FORMAL LABOR MARKET - Silva Júnior, Luiz Honorato da; Costa, Thérèse Hofmann Gatti Rodrigues; Belloni, José Angelo (Perspectivas em Gestão & Conhecimento, 2020)
The objective of this work is to follow the egress from “Escola do Trabalhador”, analyzing its dynamics in the job market. The understanding of this dynamic can be very useful for future actions within and beyond the School, including proposing new actions, and more comprehensively in the professional qualification policy. Using the official databases of formal employment, RAIS and CAGED, the performance of workers trained in the “Escola do Trabalhador” was compared to others. The results indicate that the egress from the School has achieved better results of employability in relation to others.